Cordycepin and its Nucleoside Analogs for the Treatment of Systemic COVID-19 Infection - Chellapandi, P.; Saranya, S. (Coronaviruses, 2022)
Coronavirus disease (COVID-19) pandemic is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a new coronavirus isolated from Wuhan, China. It is a global health emergency, and there is no effective antiviral therapeutics available to date. Continuous structural genomic insights of SARS-CoV-2 proteins provide a warranty for the development of rational- based antivirals. Nevertheless, a structure-based drug candidate with multiple therapeutic actions would be a practical choice of medication in the treatment of severe COVID-19 patients. Cordycepin from medicinal fungi (Cordyceps spp.) and its nucleoside analogs targeting viral RNAdependent RNA polymerase and human RNase L have potent antiviral activity against various human viruses with additional immunomodulatory and anti-inflammatory effects. Anti-inflammation treatment is of pivotal importance and should be timely tailored to the individual patient along with antivirals. Our perspective on the combined antiviral and anti-inflammatory effects of cordycepin and its analogs suggests them as new therapeutics in the treatment of systemic COVID-19 infection.
Keywords: medicinal fungi